Utilization of Siam Weed leaves (Chromolaena odorata L.) as natural dyes - Dulmalik, Dulmalik; Rosliani, Selli; Rosliana, Sella (Journal of Engineering and Applied Technology, 2021)
Siam Weed leaves can be used as natural dyes since they contain tannin compounds which give a brown color to the dyeing of fabrics. This study was conducted to utilize Siam Weed leaves as a natural dye substitute for synthetic cotton cloth and obtain dye from Siam Weed leaves in liquid form. The material used is a dyed cotton cloth with the extract of Siam Weed leaves. The variation of dipping time was 30 minutes and 13 hours. The types of fixators used were Ferrous Sulfate and Alum solution. The findings showed that the type of fixator can affect the color result of the fabric. The fixed fixator produces a dark green color while the Alum solution produces a yellow color. Based on the results of the dry rub test, the cloth that has been immersed in the dye for 13 hours and fixed by an Alum fixator produces the maximum color fastness value with a staining scale value of 5, 5, 5 (very good). Whereas in the wet rub test, the cloth that has been immersed in the dye for 13 hours and fixed with an Alum solution fixator produces good values with a range of values for the staining scale 4-5, 4-5, 4-5 (good). In the colorfastness test of washing cloth soap soaked for 30 minutes, the best dye fastness with a grayscale value of 4-5, 4-5, 4-5 (good). The type of fixator that has the best colorfastness in the washing test is the Alum fixator.